Clinical and pathological changes in the skin with granuloma annulare - M. G. Kharchilava; V. R. Khairutdinov; I. E. Belousova; A. V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Granuloma annulare (GA) is a dermatosis of unknown etiology, which has distinctive clinical and histological features. In this article, we present current information about the etiology, pathogenesis, clinical picture and pathomorphological signs of GA, as well as conduct differential diagnosis of GA with diseases that have a similar clinical and histological picture.